(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Alcoholism is a growing public health concern in India, significantly influenced by various socio-economic factors. This study explores the determinants and health implications of alcohol consumption in Kanyakumari district, Tamil Nadu—a region known for its high literacy rates and unique cultural composition. Through a mixed-method approach combining quantitative surveys and qualitative interviews with affected individuals, healthcare workers, and community leaders, the research identifies key drivers of alcoholism, including poverty, low educational attainment, occupational stress, and cultural normalization of alcohol use. The findings reveal a strong correlation between unemployment, low income, and increased alcohol dependency, particularly among daily wage earners and fishermen. Additionally, the study highlights alarming health consequences such as liver diseases, mental health disorders, and a rise in domestic violence and family disintegration. The economic burden on households and the healthcare system is also significant, often leading to cycles of poverty and marginalization. The research underscores the urgent need for multi-sectoral interventions—ranging from stricter alcohol regulation and community education to improved access to de-addiction services. Targeted policies and awareness programs tailored to local socio-cultural dynamics are essential to address this complex issue. The study concludes that addressing the socio-economic roots of alcoholism is crucial not only for individual well-being but also for the holistic development of the Kanyakumari district.